Chronic toxicity of triazine-based and non-triazine ultraviolet filters toward Chlorella vulgaris: Low ecological risk of triazine-based compounds - Yuhao Yan; Hong Gao; Rundong Chen; Zhigang Wang; Cheng Zeng; Jia Yuan; Jianjun Liu; Rong Chen (Bioresource Technology, 2026)

RNA-binding protein BICC1 promotes gastric cancer progression via the PRRX1-MAPK signaling axis - Yuanxin Xing; Rong Fan; Xiuzhen Jiang; Wenshuai Zhu; Fubo Jing; Xiaoli Ma; Yunshan Wang; Yanfei Jia (Functional & Integrative Genomics, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Robust retrieval of inland water nitrogen and phosphorus: De-biasing satellite-in situ matchups and integrating environmental constraints - Xihua Wang; Xingyu Zhu; Y. Jun Xu; Yongjiu Feng; Rong Huang; Chenyi Shi; Chengming Luo; Boyang Mao; Shunqing Jia; Qinya Lv; Zejun Liu; Xuming Ji; et al. (Journal of Water Process Engineering, 2026)

Intensive anthropogenic activities control the spatiotemporal heterogeneity of river eutrophication at the watershed scale - Xihua Wang; Shunqing Jia; Y. Jun Xu; Chaomeng Dai; Nianqing Zhou; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Hydrology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Mechanical behaviour, deformation mechanisms and support optimization of tunnels in gentle dip layered rock after freeze–thaw cycles - Xiao-Hu Zhang; Jia-Bing Zhang; Jun-Bin Fu; Rong-Huan Du; Han-Lin Wang (Tunnelling and Underground Space Technology, 2026)

Knockout of Resilin-like genes results in diminished wing size in silkworm moths - Tingting Tian; Chunxia Xiao; Haonan Dong; Qinglang Wang; Jia Fang; Zhonghui Dong; Yiran Zhu; Qingyu Rong; Yong Hou (Journal of Insect Physiology, 2026)

Sinocrassula zhaotongensis (Crassulaceae), a New Species From China - Ling‐Nan Wei; Jing Zhao; Jian‐Rong Zhang; Zi‐Xian Liu; Jia‐Guan Wang (New Zealand Journal of Botany, 2026)
Sinocrassula zhaotongensis , a new species of Crassulaceae from Yunnan Province, China, is described and illustrated. Morphologically, S. zhaotongensis is characterized by a glabrous plant surface, asymmetrically triangular to lanceolate basal leaves, triangular‐lanceolate sepals, and triangular petals that are yellowish at the base with dense purple‐red stripes and spots on the surfaces upward. Phylogenetic analyses based on concatenated chloroplast and nuclear DNA sequences strongly support S. zhaotongensis as a distinct lineage and sister to S. adpressa .

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Partitioned identification of vegetation drivers and their interactions in the Loess Plateau via interpretable XGBoost-SHAP - Yi Ren; Jia Tian; Xuejuan Feng; Guowei Wu; Caifeng He; Wei Bao; Tao Yu; Jiahui Gao; Tao Wang; Jian Wen; Rong Tao (Environment, Development and Sustainability, 2026)

3D aerial thermal mapping of smouldering coal gangue dump based on GAN super-resolution reconstruction and RGB-T image fusion and detail enhancement - Zhenlu Shao; Zhaolong Wang; Rong Deng; Zichao Jia (International Journal of Remote Sensing, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Climate change during the early Middle Jurassic: Evidence from coal-bearing strata of the Ordos Basin - Nian-De Shang; Jing-Jing Liu; Shi-Feng Dai; Ian T. Graham; Qiu-Chan Han; Rong-Kun Jia; Jia-Wei Feng; Meng-Da Yao; Yan Wang (Palaeoworld, 2026)

Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zheng Huang (Fuel, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Biochar–bentonite composite enabling antibiotic removal and greenhouse gas mitigation in waters - Yan Sun; Xiang Jia; Le Dai; Wei Ding; Yongjie Wang; Jin Zhang; Huan He; Nan Rong; Pei Lei (Chemical Engineering Journal, 2026)

Granite weathering revealed by magnesium isotopes fractionation: Implications for the flux dynamics and global carbon sink - Kai Luo; Jin-Long Ma; Fang-Zhen Teng; Gang-Jian Wei; Guan-Hong Zhu; Jia-Rong Liu; Zhuo-Ying Zhang; Zhi-Bing Wang (Chemical Geology, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Illumination-induced restructuring of extracellular polymeric substances from Klebsiella Sp. HDJY-1 drives indirect photodegradation of thifensulfuron-methyl - Jiaying Gu; Yaqi Jiao; Chunnan Zhou; Junxin Jia; Siming Li; Kai Wang; Hui Li; Hongtao Shi; Qin Zhou; Rong Liu; Li Li (Water Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Sodium alginate bead flotation assisted by cationic cellulose nanofibers for polystyrene microplastic removal - Linjuan Zhang; Hao Wen; Kemin Wei; Xichen Zheng; Jia He; Manli Wang; Peng Wei; Shaoli Fan; Guiwen Rong (Process Safety and Environmental Protection, 2026)

Changes in flavor profiles and microbial community diversity throughout rice wine fermentation with Rhizopus oryzae from different sources - Ting Tong; Jing-Rong Hu; Zhen-Jia Li; Zi-Zhen Qin; Cai-Hua Shi; Han-Cheng Wang (International Journal of Food Microbiology, 2026)

Corrigendum to “Towards near-zero emission methanol engines: Coupled mechanisms of pollutant formation and combustion–catalysis synergistic control” [Fuel 418 (2026) 138729] - Jia Tang; Bin Guan; Lei Zhu; Shiying Chang; Jiangli Ma; Rong Wang; Dongxia Yang; Tiankui Zhu; Hanshi Qu; Bingqian Tan; Zhen Huang (Fuel, 2026)

Antioxidant peptides from porcine blood meal: Mechanisms of interaction with hemin via spectroscopy and molecular docking - Rong Jia; Juanjuan Du; Jinxuan Cao; Jinpeng Wang; Yuemei Zhang; Wendi Teng; Ying Wang (Food Chemistry, 2026)

A 1D stepped coordination polymer based on Cu4I4 units for X-ray imaging over a broad temperature range - Ji-Hui Jia; Xiang-Long Hu; Dong Liang; Qianting Wang; Rong Zhang; Can-Zhong Lu (Chemical Engineering Journal, 2026)

Osmotic regulation and evaluation of oxidative stress in Hemiboea subcapitata across three habitats of the Dehang karst valley canyon - Chen-Yao Wang; De-Wu Zeng; Jia-Yi Wang; Ping Yu; Xiang-Rong Tian (Acta Physiologiae Plantarum, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Mapping coastal aquaculture ponds in China without dependence on water levels: New insights from pond dikes derived from Sentinel-1/2 imagery - Chuanpeng Zhao; Mingming Jia; Rong Zhang; Quan Han; Chunying Ren; Zongming Wang (Environmental Impact Assessment Review, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Density inversion method combining dense residuals and Bi-LSTM structure - Wei-jia Zong; Xing-jian Wang; Rong Qi; Yang Liu; Zhong-yue Luo; Zhan-bo Liu (Applied Geophysics, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

Enzyme-triggered polyelectrolyte complex for broad-spectrum antifungal therapy and biofilm eradication - Chuming Pang; Yimin Wang; Hui Zhang; Xuan Zhou; Siga Jia; Shize Leng; Rong Liu; Liangzhi Hong (Chemical Engineering Journal, 2026)

Magnetic biochar combined with digestate bioaugmentation synergistically accelerates the recovery of a collapsed anaerobic digestion system - Bao-Shan Xing; Yong-Ning Feng; Jia-Yi Liu; Yi Zhang; Guangyin Zhen; Samir Ibrahim Gadow; Rong Chen; Xiaochang C. Wang; Yu-You Li (Chemical Engineering Journal, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

SAA-YOLO: A scale-aware attention enhanced YOLOv10 for UAV-based detection of medicinal plant Phlomoides rotata in alpine grasslands - Rong Ding; Chenghui Wang; Xuemei Wu; Guopeng Chen; Jiangkai Yang; Hongmei Jia; Shihong Zhong; Rui Gu (Computers and Electronics in Agriculture, 2026)

Hybrid prediction framework for total nitrogen in freshwater lake watershed based on the northern goshawk optimization and multiple machine learning methods: An integrated strategy from data cleaning to model optimization - Xihua Wang; Chengming Luo; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Yan Dai; Yanxin Rong; Qinya Lv; Xuming Ji (Journal of Environmental Chemical Engineering, 2026)

Synergistic effects of polystyrene microplastics and 17α-methyltestosterone on immune and oxidative stress responses in the gill and liver of Gobiocypris rarus - Yibo Jia; Lu Cao; Tongyao Li; Haiyan Zhao; Gen Chen; Zijun Xiong; Weiya Rong; Qing Liu; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; et al. (Fish & Shellfish Immunology, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

The ATG14: multi-layer autophagy control and an emerging therapeutic target in cancer - Wenbo Wang; Chujuan Yu; Fulin Sun; Ruofeng Wang; Weikai Xia; Qinghang Song; Huhu Zhang; Zhenzhen Jia; Min Zhang; Haoran Wang; Zhenxiang Wang; Rong Fu; et al. (Apoptosis, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Butyrate supplementation in sows promotes offspring embryonic muscle development by upregulating HDAC-mediated H3K27ac levels and myogenic gene expression - Hao Zuo; Chen Li; Xiaoyu Niu; Zhibo Ma; Zhifeng Wu; Zeyang Gao; Liqian Sun; Yiming Jia; Mingfei Zhu; Litong Wang; Rong Zheng; Bo Zuo (Science China Life Sciences, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Intensive anthropogenic activities drive dynamic surface water-groundwater interactions: Implications for contaminant pathways at a catchment scale - Shunqing Jia; Xihua Wang; Y. Jun Xu; Chaomeng Dai; Nianqing Zhou; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Deciphering runoff-sediment-nutrient dynamics in agricultural watersheds supplied by large feeder Rivers: A multi-scale analysis - Xihua Wang; Xuming Ji; Y. Jun Xu; Boyang Mao; Shunqing Jia; Zejun Liu; Qinya Lv; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Divergence in anthropogenic activities contributed to the eutrophication heterogeneity between river and lake at basin scale: new insights from trophic state index in Asia's largest basin (Yangtze River) - Yan Dai; Xihua Wang; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Identification of a novel selenium peptide from Oryzain α hydrolysate: Selenium-specific database establishment, sequence confirmation, and molecular interaction analysis - Xin Wang; Bailiang Xue; Rong Zhang; Lin Shi; Wei Jia (Food Bioscience, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Adulteration of animal-derived whey protein in infant formula: High-throughput screening of characteristic peptides - Lin Shi; Wei Jia; Rong Zhang; Xin Wang; Haizhen Mo (Food Research International, 2025)

Progressive cracking mechanism in natural hard structural planes under creep shear testing with lateral stress unloading - Jia-Rong Wang; Xia-Ting Feng; Jun Zhao; Cheng-Xiang Yang (Engineering Geology, 2025)

An injectable and programmable hydrogen delivery system for modulation tendon tissue in tendon-bone interface microenvironment - Tao Yuan; Fei Jin; Lili Qian; Xiaojiang Yang; Xin Yu; Zhongyang Lv; Ziying Sun; Shiwen Shen; Hong Qian; Jia Meng; Hui Jiang; Wenshuang Sun; et al. (Chemical Engineering Journal, 2025)

Novel multi-component synergistic bioink that balances biocompatibility and mechanical strength for cartilage regeneration - Zijun Ma; Wendan Jia; Xiaoyuan Wang; Rong Cheng; Lu Han; Meng Li; Xiaoning Yang; Shengbo Sang (Journal of Zhejiang University-SCIENCE B, 2025)

Prediction of ammonia and total nitrogen in large freshwater lake watershed based on small sample data and analysis of their spatiotemporal variation and driving mechanism - Chengming Luo; Xihua Wang; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Yanxin Rong; Yan Dai (Process Safety and Environmental Protection, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Unraveling nitrogen evolution characteristics and driving mechanisms of estuarine alluvial islands - Xihua Wang; Yanxin Rong; Y. Jun Xu; Qinya lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yan Dai (Journal of Contaminant Hydrology, 2025)

Novel insights to the synergistic effects of magnetic biochar in anaerobic digestion while treating synthetic organic wastewater for biomethane recovery - Zhang-Wei He; Yuan-Long Jia; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Aijie Wang; Rong Chen (Chemical Engineering Journal, 2025)

Unveiling the mystery of eutrophication prediction for large freshwater lake through Temporal Convolutional Network hybrid model - Chengming Luo; Xihua Wang; Y. Jun Xu; Shunqing Jia; Zejun Liu; Boyang Mao; Yan Dai; Yanxin Rong; Qinya Lv; Xuming Ji (Journal of Environmental Chemical Engineering, 2025)

CTAB-Assisted, controlled preparation of a CeZrOx/CuSAPO-34 catalyst and its performance for the synergistic removal of NOx and toluene from flue gas - Qian Zhou; Xuehui Jia; Rong Liu; Fangfei Liu; Han Zhang; Dan Hou; Lu Wang; Yunkuo Luo; Bichun Huang; Hong Huang; Xia Gong; Chenglong Yu (Journal of Environmental Chemical Engineering, 2025)

Photochemical oxidation mechanisms and toxicity evolution of photostable atrazine during sunlight/free chlorine process - Xiaoyan Y. Ma; Xiaoru Li; Haixiang Jia; Jiahui Kho; Jiangyong Hu; Shengjiong Yang; Rong Chen; Xiaochang C. Wang; Nan Wang (Journal of Environmental Chemical Engineering, 2025)

Platinum reduction in anaerobic biofilm-membrane bioreactor: Performance, mechanism, and biofilm microbial communities - Yue Wang; Zhuo Zhen; Rong Zhao; Hui Jia; Jie Wang (Journal of Environmental Chemical Engineering, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Multifunctional integrated separator based on electrospinning structure engineering for high-stability lithium sulfur batteries - Chaojiang Fan; Rong Yang; Bing Chen; Qing Huang; Lingjiang Kou; Jiajia Song; Yong Wang; Teng Wang; Yinglin Yan; Zhongguo Zhao; Kai Jia; Wenhu Li; et al. (Chemical Engineering Journal, 2025)

Estimating daily NOx and CO2 emissions in typical megacities of east China using TROPOMI NO2 observations - Yizhen Jia; Minghui Tao; Hongming Zhang; Pengfei Ma; Bin Zhao; Rong Li; Dejia Yin; Lijuan Zhang; Haijun Huang; Lunche Wang; Yi Wang; Liangfu Chen (Atmospheric Environment, 2025)

The negative regulated immune mechanism of Skp1-Cullin1-F-box (SCF) E3 ubiquitin ligase-mediated HOS15-dependent responses in banana - Xinyi Chen; Xingchen Jia; Ruizhou Fu; Maoli Wang; Hang Rong; Jinyi Wei; Zishu Wang; Mingyuan Wang (Plant Cell Reports, 2025)

Unveiling the crucial role of rice root iron plaque in enhancing biological nitrogen fixation via 15N-labeling DNA-SIP and metagenomics in a model study - Rong Jia; Linpeng Yu; Mengyi Wang; Yulu Wu; Shiqi Liu; Sining Zhong; Shungui Zhou (Biology and Fertility of Soils, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Impact of intensive human activities on nitrate pollution in river basins: A spatiotemporal isotopic analysis - Shunqing Jia; Xihua Wang; Y. Jun Xu; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Water Process Engineering, 2025)

Dual-quantification of the different contributions of climate change and anthropogenic activities to eutrophication of rivers and lakes in Asia's largest river basin (Yangtze River) - Xihua Wang; Yan Dai; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Chengming Luo; Yanxin Rong (Journal of Hazardous Materials, 2025)

Six new combinations in Prunus sensu lato (Rosaceae) from east Asia - Meng Li; Jia-Ning Zhou; Xian-Rong Wang; Xian-Gui Yi; Muhammad Idrees (Kew Bulletin, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Spatio-temporal variations in the supply and demand of ecosystem services with multi-scenario prediction in Guangzhou City, China - Jun Wu; Zhi-Yun Jiang; Yan-Yu Xu; Lin Lin; Rong Guo; Yi-Jia Wang (Environmental Science and Pollution Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Overexpression of anthocyanin activator LrAN2 improving black goji berry (Lycium ruthenicum) tolerant to cadmium stress - Peiyan Ai; Zhiqiang Wang; Yan Li; Rong Yang; Biao A; Yixin Jia; Yuan Zong; Ying Wang; Shaohua Zeng (Journal of Hazardous Materials, 2025)

Low-valent Cu doping optimizes Ruddlesden-Popper perovskite for accelerated levofloxacin removal: Enhanced Ni-dominated dual radical/nonradical pathways - Lei Ma; Chu-Jia Jin; Huai-Yuan Niu; Zheng-Tao Dong; Long Sui; Qian Wu; Yan-Rong Peng; Jia-jia Wang; Cheng-Gang Niu (Journal of Hazardous Materials, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Impact of cyclolinopeptide (linusorb) on oxidative stability of hot-pressed flaxseed oil and their interaction with phospholipid - Jia-hui Yu; Shao-rong Zhang; Yue Du; Du-jian Deng; Yi-kang Zhang; Jun-le Li; Li-jun Hu; Wenyi Chen; Xin Yue; Yong Wang; Jiazi Chen; Zi-zhe Cai (Food Chemistry, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

Machine learning-based design, screening, and activity validation of topoisomerase I inhibitors - Ya-Kun Zhang; Jian-Bo Tong; Jia-Le Li; Rong Wang; Yan-Rong Zeng (Molecular Diversity, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Optimization of moisture content and duration in low-speed rotational thermostatic tempering for enhanced physicochemical properties of indica rice flour - Rong Dong; Wenkang Luo; Xiwu Jia; Wenjing Huang; Jian Xia; Zhan Wang (Journal of Cereal Science, 2025)

Multi-machine learning methods for rapid and synergistic inversion of groundwater contamination source, hydrogeologic parameter and boundary condition - Chengming Luo; Xihua Wang; Y. Jun Xu; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Yanxin Rong; Yan Dai (Journal of Contaminant Hydrology, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Synergistic estimation of mangrove canopy height across coastal China: Integrating SDGSAT-1 multispectral data with Sentinel-1/2 time-series imagery - Mingming Jia; Rong Zhang; Chuanpeng Zhao; Yaming Zhou; Chunying Ren; Dehua Mao; Huiying Li; Genyun Sun; Hongsheng Zhang; Wensen Yu; Zongming Wang; Yeqiao Wang (Remote Sensing of Environment, 2025)

Adsorption behavior and mechanism of cadmium, copper, and lead on polylactic acid microplastics exposed to ultraviolet light - Fang Feng; Shutao Wang; Xue He; Xinghua Wang; Jia Huang; Guiming Liu; Sashuang Rong; Shiming Su; Hongyuan yan; Bing Han; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Bismuth tungstate/graphite carbon nitride composites for efficient photocatalytic reduction of U(VI): Synthesis, performance, and mechanism - Yu-Jia Xiao; Shi Chen; Ping Li; Dong Zhang; Jing-Jing Wang; Hui Dong; Yan-Rong He (Journal of Environmental Chemical Engineering, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Exogenous melatonin enhancing the accumulation of flavonoids and carotenoids in wolfberry fruit at cold storage - Rong Jiang; Zhiqiang Wang; Yixin Jia; A. Biao; Yuan Zong; Chao Yang; Minglin Li; Hongjiao Wang; Yuling Zhao; Ying Wang; Shaohua Zeng (Food Research International, 2025)

Unlocking China's grain yield potential: Harnessing technological and spatial synergies in diverse cropping systems - Zhen-Zhong Dai; Sen Chang; Guo-Rong Zhao; Jia-Jia Duan; Hao-Yuan Liang; Zhi-Yuan Zhu; Sheng-Li Liu; Yong-Zhong Feng; Xing Wang (Agricultural Systems, 2025)

Genomic characterization of a novel gammapartitivirus infecting the phytopathogenic fungus Colletotrichum cliviicola - Ya Rong Wang; Jie Zhong; Zhijuan Yang; Yi Chen; Jia En Su (Archives of Virology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Combining POA-VMD for multi-machine learning methods to predict ammonia nitrogen in the largest freshwater lake in China (Poyang Lake) - Chengming Luo; Xihua Wang; Y. Jun Xu; Cong Wang; Qinya Lv; Xuming Ji; Boyang Mao; Shunqing Jia; Zejun Liu; Yanxin Rong; Yan Dai (Journal of Water Process Engineering, 2025)

A multi-perspective understanding of population change in migratory species: A case study with pied avocets (Recurvirostra avosetta) in East Asia - Yang Wu; Weipan Lei; Entao Wu; Han Pan; Yifei Jia; Cai Lu; Yongxiang Han; Junjie Wang; Rong Fan; Zhijun Ma; Zhengwang Zhang; Richard A. Fuller (Biological Conservation, 2025)

A Global Synthesis of How Plants Respond to Climate Warming From Traits to Fitness - Pengyan Jia; Rong Zhang; Bernhard Schmid; Han Wang; Jin‐Sheng He; Jiaxi Liu; Sijie Liu; Sipeng Jian; Yanhao Feng (Ecology Letters, 2025)
Despite intensive research, our understanding of how plants respond to warming by coordinating their full arsenal of traits to adjust fitness is lacking. To fill this gap, we applied a trait‐based framework with three clusters (two functional clusters: “carbon‐fixation rate” and “carbon‐fixation area”; a third cluster: “total carbon fixation”) to a global dataset compiled from 572 studies of warming experiments with 677 species and a comprehensive list of traits and fitness components. The pairwise correlation analysis complemented with SEM and PCA showed that plants increased biomass (the core variable in the third cluster) under warming by coordinating satellite traits in two functional clusters to adjust their core traits, net photosynthesis rate and total leaf area, respectively. In particular, the trait coordination was characterised by the maintenance of net photosynthesis rate and the increase of total leaf area, which was robust across ecological contexts although warming responses of the variables per se displayed context‐dependences. Moreover, the trade‐offs between biomass and reproduction (itself bearing mass vs. number trade‐offs) in their warming responses scaled the coordination to enhance fitness except in the contexts where reproduction was reduced. These findings could help explain and predict plant form and function in a warming world.

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Quantitative characterization of global nighttime light: A method for measuring energy intensity based on radiant flux and SNPP-VIIRS data - Haihang Zeng; Mingming Jia; Xiangyu Ning; Zhaohui Xue; Rong Zhang; Chuanpeng Zhao; Yangyang Yan; Zongming Wang (Remote Sensing of Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Biorecovery of platinum group metals to nanoparticles: Current status, prospects, and challenges - Yue Wang; Zhuo Zhen; Rong Zhao; Jie Yang; Hui Jia; Jie Wang (Journal of Environmental Chemical Engineering, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Unveiling the molecular symphony: MicroRNA160a-Auxin Response Factor 18 module orchestrates low potassium tolerance in banana (Musa acuminata L.) - Yi Tang; Hang Rong; Xingchen Jia; Yinglong Chen; Zishu Wang; Jinyi Wei; Chenyi Yang; Jianfu Liu; Mingyuan Wang; Hailing Yu; Qizhi Wang (Plant Science, 2025)

Sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Min Tan; Li-Zhong Wang; Jun-Jie Hao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2025)

Occurrence characteristics and factors that influence shale oil in the Jurassic Lianggaoshan Formation, northeastern Sichuan Basin - Xuefeng Bai; Xin Wang; Min Wang; Junhui Li; Shuangfang Lu; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Youzhi Wang (Marine and Petroleum Geology, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Effects of the types and ages of vegetation restoration on land surface roughness in the Eastern Hobq Desert, Northern China - Ji Feng; Yong-Sheng Wu; Li-Yuan Lu; Chasina Xi; Feng-Yan Wu; Chao-Yu Wang; Qiang Yin; Altantuya Dorjsuren; Rong-Liang Jia; Yu Qiao; Yuan-Fa Meng; Jie Yu (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Recycle of residual ammonium from weathered crust elution-deposited rare earth tailings via an efficient combined method of elution, struvite precipitation and on-line adsorption - Kejia Wu; Junxia Yu; Jia Wang; Xiaodi Li; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Journal of Water Process Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Advancing mangrove species mapping: An innovative approach using Google Earth images and a U-shaped network for individual-level Sonneratia apetala detection - Chuanpeng Zhao; Yubin Li; Mingming Jia; Chengbin Wu; Rong Zhang; Chunying Ren; Zongming Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Meet-in-metabonomics: Insights into associations between hair heavy metal and adverse child growth in e-waste recycling area - Hong-Xuan Kuang; Meng-Yang Li; Jia-Rong Wang; Jian-Hua Tan; Wen-Yao Liang; Yang Zhou; Yun-Jiang Yu (Environmental Pollution, 2024)

Data mining-based identification of epigenetic signatures with discrimination potential of lung adenocarcinoma and squamous cell carcinoma - Wen-guang Pang; Min Ye; Jia-rong Chen; Liang Zhang; Zheng Wang (Molecular Biology Reports, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Effects of 2,4,6-Trichloroanisole on the morphological development and motility of zebrafish - Yanxia Zuo; Fang Zhou; Rong Huang; Zhihui Jia; Juhong Xie; Guangxin Wang; Shuzhao Jia; Yongming Li; Manyi Wang; Lanjie Liao; Feng Ge; Yaping Wang (Science of The Total Environment, 2024)

Recovery of platinum nanoparticles by the anaerobic mixed consortium: Platinum (IV) ion reduction, microbial community dynamics and functional genes identification - Yue Wang; Rong Zhao; Zhuo Zhen; Jie Yang; Hui Jia; Jie Wang (Journal of Water Process Engineering, 2024)

Transfer from ciliate to zebrafish: Unveiling mechanisms and combined effects of microplastics and heavy metals - Yan Zhang; Caixia Wang; Ruiqi Jia; Hongan Long; Jianfeng Zhou; Gaojingwen Sun; YunLong Wang; Zhaoji Zhang; Xiaozhi Rong; Yong Jiang (Journal of Hazardous Materials, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

Improving curcumin bioavailability: Targeted delivery of curcumin and loading systems in intestinal inflammation - Junyi Zhao; Wei Jia; Rong Zhang; Xin Wang; Li Zhang (Food Research International, 2024)

Navigating the trade-offs in crop production and soil quality through alternative cropping - Junlong Huang; Yi Xu; Mengsu Peng; Rong Jia; Juncong Chu; Amit Kumar; Changzhong Ren; Yadong Yang; Dongmei Wang; Xiaojun Wang; Zhaohai Zeng; Leanne Peixoto; et al. (Field Crops Research, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Lithium-ion battery future degradation trajectory early description amid data-driven end-of-life point and knee point co-prediction - Ganglin Cao; Yao Jia; Shouxuan Chen; Yuanfei Geng; Shuzhi Zhang; Haibin Lu; Rong Feng; Ning Wang; Xiongwen Zhang (Journal of Cleaner Production, 2024)

Solar-driven spherical sandwiched hydrogel with reversible phase transition-induced egg-structure for highly efficient and stable water harvesting and purifying - Jiangyang Mei; Yong Jin; Haonan Chen; Rong Zhou; Zhexian Mao; Jia Wang (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

OsHRZ1 negatively regulates rice resistant to Magnaporthe oryzae infection by targeting OsVOZ2 - Jia-ying Sun; Zeng-ran Zhou; Yu-qi Wang; Dong-yu Zhu; Dian-rong Ma (Transgenic Research, 2024)

Tracking the impact of perfluoroalkyl acid emissions on antibiotic resistance gene profiles in receiving water by metagenomic analysis - Nannan Lu; Zhenqi Du; Fumin Chu; Rong Xiao; Zhengdi Wu; Mingquan Wang; Ruibao Jia; Wenhai Chu (Water Research, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

MaHOS15 negatively regulates plant immune defense induced by banana fusarium wilt via salicylic acid pathway - Xingchen Jia; Kelin Chen; Yinglong Chen; Yi Tang; Hang Rong; Ping Lin; Yuhao Zhou; Chuqiao Wang; Mingyuan Wang; Jianfu Liu; Qizhi Wang; Hailing Yu (Physiological and Molecular Plant Pathology, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Water-soluble metal-organic cages crosslinked injectable hydrogel for multi-modal synergistic therapy - Wen-Zhen Li; Xiao-Fan Rong; Yu Wang; Jia-Wen Xiong; Na Zhou; Zi-Xin Wang; Xi-Jia Fang; Wenjing Wang; Yi Liu; Xiao-Qiang Wang (Chemical Engineering Journal, 2024)

Surface PD-1 expression in T cells is suppressed by HNRNPK through an exonic splicing silencer on exon 3 - Jiayun Wang; Lingyan Yan; Xu Wang; Rong Jia; Jihua Guo (Inflammation Research, 2024)

NCOA4-mediated ferritinophagy participates in cadmium-triggered ferroptosis in spermatogonia - Didi Jia; Mingming Zhang; Mengyuan Li; Wenjing Gong; Wei Huang; Rong Wang; Yihang Chen; Qizi Yin; Jie Wu; Zhongxiu Jin; Juan Wang; Yehao Liu; et al. (Toxicology, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

Mangrove species mapping in coastal China using synthesized Sentinel-2 high-separability images - Chuanpeng Zhao; Mingming Jia; Rong Zhang; Zongming Wang; Chunying Ren; Dehua Mao; Yeqiao Wang (Remote Sensing of Environment, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Nighttime light in China's coastal zone: The type classification approach using SDGSAT-1 Glimmer Imager - Mingming Jia; Haihang Zeng; Zuoqi Chen; Zongming Wang; Chunying Ren; Dehua Mao; Chuanpeng Zhao; Rong Zhang; Yeqiao Wang (Remote Sensing of Environment, 2024)

Massive early Middle Pleistocene cheetah from eastern Asia shed light onto the evolution of Acinonyx in Eurasia - Qigao Jiangzuo; Yaming Wang; Joan Madurell-Malapeira; Saverio Bartolini Lucenti; Shijie Li; Shiqi Wang; Zhaoyu Li; Rong Yang; Yi Jia; Lu Zhang; Shanqin Chen; Changzhu Jin; et al. (Quaternary Science Reviews, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Artificial infection pathway of largemouth bass LMBV and identification of resistant and susceptible individuals - Ya Zhang; Bin Gui; Zhihui Jia; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Reservoir characteristics and controlling factors of the middle–high maturity multiple lithofacies reservoirs of the Lianggaoshan Formation shale strata in the northeastern Sichuan basin, China - Xin Wang; Min Wang; Chen Zhao; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Xinbin Zhao; Yulong Tang (Marine and Petroleum Geology, 2024)

Photo-driven dynamic hydrogel modulates bone marrow mesenchymal stem cells behavior for enhanced cartilage regeneration - Wenjie Zhang; Wenliang Xue; Zhaoli Jia; Rong Yang; Penghui Wang; Yi Hu; Xiaoyan Tan; Qiang Chen; Bo Chi (Chemical Engineering Journal, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Evidence for the transportation of aggregated microplastics in the symplast pathway of oilseed rape roots and their impact on plant growth - Sashuang Rong; Shutao Wang; Hongmei Liu; Yuxin Li; Jia Huang; Wanqing Wang; Bing Han; Shiming Su; Wei Liu (Science of The Total Environment, 2024)

Experiment and dynamic simulation of hydrogen recovery from hydrogen-containing gas mixtures via hydrate-membrane coupling method - Jingbo Gao; Qiang Sun; Jia Luo; Leyan Li; Ninghui Liu; Rong Ma; Hang Zhao; Xiangming Li; Zongyu Qin; Yiwei Wang; Xuqiang Guo (Fuel, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Preparation of potential organic fertilizer rich in γ-polyglutamic acid via microbial fermentation using brewer's spent grain as basic substrate - Fengqing Wang; Yanmei Chen; Jia Zheng; Can Yang; Li Li; Rong Li; Meilin Shi; Zhongxuan Li (Bioresource Technology, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Quantifying synergies and trade-offs in the food-energy-soil-environment nexus under organic fertilization - Yi Xu; Bolun Luo; Rong Jia; Jing Xiao; Xiquang Wang; Yadong Yang; Shuai Xue; Zhaohai Zeng; Robert W. Brown; Huadong Zang (Journal of Environmental Management, 2024)

Excavation, identification and structure-activity relationship of heat-stable umami peptides in the processing of Wuding chicken - Rong Jia; Yuan Yang; Guozhou Liao; Dahai Gu; Yuehong Pu; Ming Huang; Guiying Wang (Food Chemistry, 2024)

Two birds with one stone: A magneto-optical dual-stimuli-responsive intelligent Pickering emulsion for efficient conversion of glucose to 5-hydroxymethylfurfural - Zhong-Qiu Liu; Jia-Liang Guo; Rong-Hua Liang; Feng-Xiang Wang; Zhan-Ku Li; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Application of pesticide application measures to reduce residue based on the metabolic transfer law of imidacloprid in banana leaves and soil - Lvyun Zhuang; Xiaopeng Wu; Daizhu Lyu; Mingyue Wang; Ruohao Zhou; Jia Song; Yu Rong (Chemosphere, 2023)

A novel supported Mn-Ce catalyst with meso-microporous structure for low temperature synergistic removal of nitrogen oxides and toluene: structure–activity relationship and synergistic mechanism - Chenglong Yu; Xuehui Jia; Rong Liu; Hansun Fang; Jinliang Wang; Danping Li; Jiangbo Xiong; Junhui Dan; Zhenhua Dai; Lu Wang (Chemical Engineering Journal, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Characterization of the Oral Microbiota in Captive Sichuan Golden Snub-nosed Monkeys (Rhinopithecus roxellana) of Different Ages - Rong Chen; Xinyi Liu; Meirong Li; Xiaojuan Xu; Ran Lv; Yuanyuan Chen; Guodong Wang; Changlin Deng; Nan Chen; Ting Jia; Siteng Wang; Guangjin Liu (International Journal of Primatology, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Adaptability law of central heating environment under the effect of thermal history: A continuous field survey - Chao Jia; Xihao Bie; Chang Sun; Zhicheng Zhang; Yonghua Rong; Jing Cao; Menghan Wang (Building and Environment, 2023)

In-situ constructing amidoxime groups on metal-free g-C3N4 to enhance chemisorption, light absorption, and carrier separation for efficient photo-assisted uranium(VI) extraction - Kaifu Yu; Yi Li; Xin Cao; Ruixiang Wang; Li Zhou; Linzhen Wu; Ningning He; Jia Lei; Dengjiang Fu; Tao Chen; Rong He; Wenkun Zhu (Journal of Hazardous Materials, 2023)

Inactivation of airborne pathogenic microorganisms by plasma-activated nebulized mist - Li Guo; Pengyu Zhao; Yikang Jia; Zifeng Wang; Min Chen; Hao Zhang; Dingxin Liu; Yong Zhang; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2023)

Impact of bentonite on greenhouse gas emissions during pig manure composting and its subsequent application - Jia-Ping Wu; Meng-Ling Li; Yan Wang; Shan Lin; Rong-Gui Hu; Rong-Biao Xiang (Journal of Environmental Management, 2023)

Identification of umami peptides from Wuding chicken by Nano-HPLC-MS/MS and insights into the umami taste mechanisms - Rong Jia; Ying He; Guozhou Liao; Zijiang Yang; Dahai Gu; Yuehong Pu; Ming Huang; Guiying Wang (Food Research International, 2023)

In vitro adventitious regeneration and plantlet transplantation of Atractylodes chinensis (DC.) Koidz., a valuable medicinal plant - Wenhao Jia; Junbo Rong; Mengyang Zhang; Wenyue Peng; Xutong He; Xiujuan Lei; Yingping Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Freeze-thaw treatment of bacteria significantly affects bacterial transport behaviors in both saturated and unsaturated porous media: Deep investigation the roles of flagella and extracellular polymeric substances - Lei He; Jianmei Qin; Jia Guo; Shuai Wang; Haifeng Rong; Meiping Tong (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Progress and perspective in enrichment and separation of radionuclide uranium by biomass functional materials - Jia Lei; Huanhuan Liu; Li Zhou; Yazhou Wang; Kaifu Yu; Hui Zhu; Bo Wang; Mengxuan Zang; Jian Zhou; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Performance evaluation of a novel relay parallel push-pull ventilation system for long-distance pollution control - Yu Zhou; Wan-Rong Ren; Zhiyuan Li; Yuxin Fang; Lei Jia; Yi Wang (Building and Environment, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Effects of dietary supplementation of Anabaena sp. PCC7120 expressing VP28 protein on survival and histopathology after WSSV infection in Macrobrachium nipponense - Yupei Tong; Jia Yang; Li Wang; Xiaoping Chi; Chan Zhu; Rong Yin; Le Zhang; Yaru Li; Chunyan Zhao; Rui Jia (Fish & Shellfish Immunology, 2023)

People's psychological and physiological responses to the combined smell-thermal environments - Chao Jia; Yonghua Rong; Xiaoying Geng; Menghan Wang; Zhicheng Zhang; Shengnan Han; Xihao Bie (Building and Environment, 2023)

NKD1 targeting PCM1 regulates the therapeutic effects of homoharringtonine on colorectal cancer - Jia Cao; Xiang Tao; Bin Shi; Jia Wang; Rong Ma; Jufen Zhao; Jinhai Tian; Qi Huang; Jingjing Yu; Libin Wang (Molecular Biology Reports, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Characteristics and comparisons of the aerobic and anaerobic denitrification of a Klebsiella oxytoca strain: Performance, electron transfer pathway, and mechanism - Cheng-jia Ju; Shareen Niyazi; Wen-yin Cao; Quan Wang; Rong-ping Chen; Lei Yu (Journal of Environmental Management, 2023)

PSMD4 drives progression of hepatocellular carcinoma via Akt/COX2 pathway and p53 inhibition - Jiamin Zhang; Shu Fang; Fanghao Rong; Miaomiao Jia; Yunpeng Wang; Huixian Cui; Peipei Hao (Human Cell, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Effects of dissolved organic matter derived from two herbs on the growth, physiology, and physico-chemical characteristics of four bloom-forming algae species - Rong Xiang; Tingting Liu; Zhaosheng Chu; Xing Wang; Binghui Zheng; Haifeng Jia (Journal of Environmental Management, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Monitoring the light pollution changes of China’s mangrove forests from 1992-2020 using nighttime light data - Haihang Zeng; Mingming Jia; Rong Zhang; Zongming Wang; Dehua Mao; Chunying Ren; Chuanpeng Zhao (Frontiers in Marine Science, 2023)
Mangrove forests are one of the most biologically diverse and productive ecosystems on Earth. They are important breeding and nursing grounds for amphibians, invertebrates, birds, fish, etc. Light pollution may cause serious degradation of biodiversity in the ecosystem. A report of the long-term holistic views of light pollution changes is essential for sustainable management of mangrove ecosystems. However, to date, such studies have rarely been carried out. This study aimed to monitor the long-term light pollution changes of China’s mangrove forests. To achieve this goal, we used time-series nighttime light (NTL) data to build continuous light pollution data. NTL maps made with DMSP-OLS (DNL) or NPP-VIIRS (VNL) are widely utilized in research on human activity. However, DMSP and VIIRS images are different in spatial resolution, radiation resolution, and data saturation. Thus, this study innovatively set an optimal threshold for generating consistent light pollution data in mangrove areas from 1992-2020. The results showed that: (1) the proportion of light-polluted mangrove forests in China increased from 12% in 1992 to 52% in 2020; (2) the largest net increase occurred in Guangxi with an area of 4,086 ha, followed by Guangdong (3,365 ha) and Hainan (2,944 ha); (3) Zhejiang had the largest proportion of net growth (from 0% in 1992 to 99% in 2020), followed by Hainan (66%) and Fujian (59%). Mangrove forests have been protected and restored for decades in China; this study indicates that the establishment of nature reserves is effective in preventing the light pollution of mangroves and provides the first long-term multi-temporal dataset of light pollution in China’s mangrove forests. This comprehensive information could support related studies and facilitate the development of applicable coastal management strategies in China.

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Magnetic field-driven biochemical landscape of browning abatement in goat milk using spatial-omics uncovers - Rong Zhang; Wei Jia; Meng Zhang; Haiyan Xue; Huxuan Wang; Xixuan Wu (Food Chemistry, 2023)

Cadmium exposure during puberty damages testicular development and spermatogenesis via ferroptosis caused by intracellular iron overload and oxidative stress in mice - Yi Wang; Jie Wu; Mingming Zhang; Huijuan OuYang; Mengyuan Li; Didi Jia; Rong Wang; Weiyi Zhou; Hao Liu; Yuan Hu; Yuyou Yao; Yehao Liu; et al. (Environmental Pollution, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Efficient inactivation of the contamination with pathogenic microorganisms by a combination of water spray and plasma-activated air - Li Guo; Pengyu Zhao; Yikang Jia; Tianhui Li; Lingling Huang; Zifeng Wang; Dingxin Liu; Zhanwu Hou; Yizhen Zhao; Lei Zhang; Hua Li; Yu Kong; et al. (Journal of Hazardous Materials, 2023)

Rapid, linear, and highly reliable structural-color switching enabled by thermal regulation of chiral nematic mesophases - Dong Li; Rong-Rong Jiang; Si-Kai Chen; Jia-Min Wu; Xiu Dong; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Accidental acquisition of a rescued Japanese encephalitis virus with unspliced introns in the viral genome when using an intron-based stabilization approach - Ying Huang; Hongshan Xu; Shan Liu; Jiansheng Lu; Lili Jia; Yuhua Li; Rong Wang; Peng Yang; Yongxin Yu; Zhixin Yang (Archives of Virology, 2023)
The intron-based stabilization approach is a very useful strategy for construction of stable flavivirus infectious clones. SA 14 -14-2 is a highly attenuated Japanese encephalitis (JE) live vaccine strain that has been widely used in China since 1989. To develop safe and effective recombinant vaccines with SA 14 -14-2 as a backbone vector, we constructed the DNA-based infectious clone pCMW-JEV of SA 14 -14-2 using the intron-based stabilization approach and acquired the rescued virus rDJEV, which retained the biological properties of the parental virus. Unexpectedly, a rescued virus strain with altered virulence, designated rHV-DJEV, was accidentally acquired in one of the transfection experiments. rHV-DJEV showed up to 10 5 -fold increased neurovirulence compared with the SA 14 -14-2 parental strain. Genome sequencing showed that the inserted introns were still present in the genome of rHV-DJEV. Therefore, we think that the intron-based stabilization approach should be used with caution in vaccine development and direct iDNA immunization.

Functional insights of a two-component system sensor kinase GacS in a fish pathogen, Pseudomonas plecoglossicida - Su-Ming Zhou; Yan Wang; Feng-Ling Shu; Zhen Tao; Xiao Xie; Jia-Song Xie; Rong-Rong Ma; Fei Yin (Aquaculture, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Hominibacterium faecale gen. nov., sp. nov., an anaerobic l-arginine-degrading bacterium isolated from human feces - Noori Borhanudin; Min Yang; Andrei V. Chaplin; Jiang Li; Qiong Wang; Li-rong Dai; Ke-jia Wu; Shi-chun Ma; Boris A. Efimov; Lei Cheng (Archives of Microbiology, 2023)

Marine Radar Oil Spill Extraction Based on Texture Features and BP Neural Network - Rong Chen; Baozhu Jia; Long Ma; Jin Xu; Bo Li; Haixia Wang (Journal of Marine Science and Engineering, 2022)
Marine oil spills are one of the major threats to marine ecological safety, and the rapid identification of oil films is of great significance to the emergency response. Marine radar can provide data for marine oil spill detection; however, to date, it has not been commonly reported. Traditional marine radar oil spill research is mostly based on grayscale segmentation, and its accuracy depends entirely on the selection of the threshold. With the development of algorithm technology, marine radar oil spill extraction has gradually come to focus on artificial intelligence, and the study of oil spills based on machine learning has begun to develop. Based on X-band marine radar images collected from the Dalian 716 incident, this study used image texture features, the BP neural network classifier, and threshold segmentation for oil spill extraction. Firstly, the original image was pre-processed, to eliminate co-channel interference noise. Secondly, texture features were extracted and analyzed by the gray-level co-occurrence matrix (GLCM) and principal component analysis (PCA); then, the BP neural work was used to obtain the effective wave region. Finally, threshold segmentation was performed, to extract the marine oil slicks. The constructed BP neural network could achieve 93.75% classification accuracy, with the oil film remaining intact and the segmentation range being small; the extraction results were almost free of false positive targets, and the actual area of the oil film was calculated to be 42,629.12 m2. The method proposed in this paper can provide a reference for real-time monitoring of oil spill incidents.

Associations of essential element serum concentrations with autism spectrum disorder - Jing Wu; Dongfang Wang; Lailai Yan; Meixiang Jia; Jishui Zhang; Songping Han; Jisheng Han; Jingyu Wang; Xi Chen; Rong Zhang (Environmental Science and Pollution Research, 2022)

Tetramethylpyrazine protects neural stem cells against sevoflurane-induced toxicity through Akt/GSK-3β pathway - Yan Feng; Kui Wang; Ning Wang; Pengyu Jia; Lei Zhang; Haozheng Yuan; Pan Lu; Yang Lu; Hong Zhang; Rong Li; Yan Zhang; Qianqian Li; et al. (Metabolic Brain Disease, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Three new C 21 steroidal glycosides isolated from Metaplexis japonica and their potential inhibitory effects on tyrosine protein kinases - Xu Wang; Qing-Yun Ma; Chen Liu; Jia Yang; Qing-Tao Lv; Zhen-Hua Tian; Hai-Qiang Jiang; Rong Rong (Natural Product Research, 2022)

A novel alkaloid from the seeds of Sophora alopecuroides L - Zi-Jian Rong; Xiao-Xu Gao; Gao-Sheng Hu; Ting Yan; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Two new species of Ceriporia (Irpicaceae, Basidiomycota) from the Asia Pacific area - Jia-Jia Chen; Ya-Rong Wang; Chao-Ge Wang; Yu-Cheng Dai (Mycological Progress, 2022)

Clinical characteristics of 967 children with pertussis: a single-center analysis over an 8-year period in Beijing, China - Limin Kang; Xiaodai Cui; Jin Fu; Wenpeng Wang; Li Li; Tiegeng Li; Xiaoying Wang; Fei Xiao; Huixue Jia; Rong Mi; Xinlin Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Lignans and phenylpropanoids from the liquid juice of phyllostachys edulis - De-Tao Wang; Ying-Ying Xue; Ying-Fang Zhang; Hang Xun; Qi-Rong Guo; Feng Tang; Jia Sun; Fei-Fei Qi (Natural Product Research, 2021)

Aquamicrobium zhengzhouense sp. nov., a Bacterium Isolated from Farmland Soil Applied with Amino Acid Fertilizer - Xiang Wang; Chun-Fu Zhou; Jia-Rong Cheng; Sheng-Fei Cao; Hong-Xing Yang; Jian-Rong Zhao (Current Microbiology, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Growth influence of juvenile golden trout (Oncorhynchus mykiss) in different osmotic conditions: implications for tissue histology, biochemical indicators, and genes transcription involved in GH/IGF system - Baoliang Bi; Yu Gao; Dan Jia; Lingfu Kong; Yanhua Su; Hua Rong; Xiangwei Wu; Xiaowen Wang; Zhuoyong Hu; Qing Hu (Fish Physiology and Biochemistry, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Patterns of intrinsic brain activity in essential tremor with resting tremor and tremor-dominant Parkinson’s disease - Jun-ying Li; Zhong-jiao Lu; Xue-ling Suo; Nan-nan Li; Du Lei; Ling Wang; Jia-xin Peng; Li-ren Duan; Jing Xi; Yi Jiang; Qi-yong Gong; Rong Peng (Brain Imaging and Behavior, 2020)

The effects of misregistration between hyperspectral and panchromatic images on linear spectral unmixing - Xiaoyu Cheng; Yueming Wang; Jianxin Jia; Maoxing Wen; Rong Shu; Jianyu Wang (International Journal of Remote Sensing, 2020)

Physiological and transcriptional response to heat stress in heat-resistant and heat-sensitive maize (Zea mays L.) inbred lines at seedling stage - De-Chuan Wu; Jia-Fei Zhu; Zhong-Ze Shu; Wei Wang; Cheng Yan; Shan-Bin Xu; De-Xiang Wu; Cheng-Yu Wang; Zhao-rong Dong; Genlou Sun (Protoplasma, 2020)

Probiotic and Safety Properties Screening of Enterococcus faecalis from Healthy Chinese Infants - Juan Wang; Rong Da; Xiaohong Tuo; Yue Cheng; Jie Wei; Kaichong Jiang; Jia Lv; Omolade Monisayo Adediji; Bei Han (Probiotics and Antimicrobial Proteins, 2020)

Induction of thoracic aortic dissection: a mini-review of β-aminopropionitrile-related mouse models - Hai-qiong Zheng; Jia-bing Rong; Fei-ming Ye; Yin-chuan Xu; Hong S. Lu; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2020)

Influence of mature El Niño‐Southern Oscillation phase on seasonal precipitation and streamflow in the Yangtze River Basin, China - Jia Wei; Weiguang Wang; Quanxi Shao; Yanshu Rong; Wanqiu Xing; Catherine Liu (International Journal of Climatology, 2020)
As one of the most influential oceanic and atmospheric oscillations in the Earth system, El Niño‐Southern Oscillation (ENSO) has modulated numerous geophysical processes. This is particularly true for the Yangtze River Basin (YRB), which is vulnerable to Asian Monsoon and faces serious hydrological hazards. In this study, the co‐variability between lag–lead precipitation and sea surface temperature anomalies was evaluated utilizing singular value decomposition (SVD) method. Moreover, certain teleconnections between ENSO and streamflow were identified by wavelet methods. In addition, the contribution of related atmospheric variables was revealed by composite analysis. Results indicate that there are strong associations in lag–lead seasons between the wet condition (dry condition) and September–November (December–February) mature ENSO phase. Significant common power and coherence signals between the ENSO indices and the streamflow occur in the 4–8, 8–16 and 16–32 seasonal scales. Meanwhile, the activity cycle of the ENSO indices ahead of streamflow increases from the mid‐lower reaches to the source region. In addition, the Western Pacific Subtropical High is strengthened during the mature ENSO phase. Anomalous sinking motions and divergent water vapour flux occupy the YRB, reducing the precipitation and leading to the dry condition in the source region until the following March–May. On the other hand, ascending movements and abundant water vapour flux coming from northern Pacific, equatorial western Pacific and the Bay of Bengal result in the wet condition in the mid‐lower reaches.

Translocator protein 18 kDa: a potential therapeutic biomarker for post traumatic stress disorder - Zhi-Kun Qiu; Xu Liu; Yong Chen; Rong-Jia Wu; Shi-Feng Guan; Yun-yun Pan; Qian-Bo Wang; Dan Tang; Tao Zhu; Ji-Sheng Chen (Metabolic Brain Disease, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Fate of 2,4,6-Tribromophenol in Soil Under Different Redox Conditions - Xiong Jia; Wenji Wang; Yao Yao; Yujie He; Philippe F.-X. Corvini; Rong Ji (Bulletin of Environmental Contamination and Toxicology, 2020)

Toonapolyynes A–D, new polyynes from Toona ciliata - Rong Wang; Fu-Qiang Ni; Jun Sang; Yao Zhang; Jia-Luo Huang; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2020)

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

AtJ3, a specific HSP40 protein, mediates protein farnesylation-dependent response to heat stress in Arabidopsis - Jia-Rong Wu; Tzu-Yun Wang; Chi-Pei Weng; Ngoc Kieu Thi Duong; Shaw-Jye Wu (Planta, 2019)

Fluorescence “Off-On” Probe for L-Cysteine Detection Based on Nitrogen Doped Carbon Dots - Yin-long Xu; Rong-biao Bai; Cai-yu Qi; Zeng Ren; Xiu-zhi Jia; Zi-gui Kan; Cao-long Li; Fei Wang (Journal of Fluorescence, 2019)

HL2 on chromosome 7D of wheat (Triticum aestivum L.) regulates both head length and spikelet number - Hongni Yao; Quan Xie; Shulin Xue; Jing Luo; Jikang Lu; Zhongxin Kong; Yongpan Wang; Wenling Zhai; Nan Lu; Rong Wei; Yang Yang; Yuzhou Han; et al. (Theoretical and Applied Genetics, 2019)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

A study of the characteristics of energy flux and its relationship with the summer monsoon over alpine wetlands in the source region of the Yellow River - Dongyu Jia; Jun Wen; Yaoming Ma; Juan Zhou; Jinlei Chen; Rong Liu; Xin Wang; Tangtang Zhang; Xin Lai; ZuoLiang Wang (Meteorology and Atmospheric Physics, 2019)

Extracellular ATP released by copper stress could act as diffusible signal in alleviating the copper stress-induced cell death - Ling-Yun Jia; Jing-Yue Bai; Kun Sun; Rong-fang Wang; Han-Qing Feng (Protoplasma, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

The response of metabolically active Clostridium community to initial pH shift is closely correlated with microbial Fe(III) reduction in flooded paddy soils - Lina Li; Zhi Qu; Baoli Wang; Rong Jia; Dong Qu (Journal of Soils and Sediments, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

Association between serum somatostatin levels and glucose-lipid metabolism in the Jino ethnic minority and Han Chinese population - Shiyun Wang; Rong Zhang; Xuhong Hou; Fusong Jiang; Jie Wang; Zhen He; Feng Jiang; Cheng Hu; Weiping Jia (Science China Life Sciences, 2018)

Development of an Autism Subtyping Questionnaire Based on Social Behaviors - Fan-Chao Meng; Xin-Jie Xu; Tian-Jia Song; Xiao-Jing Shou; Xiao-Li Wang; Song-Ping Han; Ji-Sheng Han; Rong Zhang (Neuroscience Bulletin, 2018)

The warm season characteristics of the turbulence structure and transfer of turbulent kinetic energy over alpine wetlands at the source of the Yellow River - Dongyu Jia; Jun Wen; Yaoming Ma; Xin Wang; Tangtang Zhang; Rong Liu; Xin Lai (Meteorology and Atmospheric Physics, 2018)

First report of tomato yellow Leaf curl virus and cucumber mosaic virus infecting Huoxiang (Agastache rugosa) in CHINA - Rong Wang; Yong Li; Jia-Li Dong; Wan-Long Ding (Journal of Plant Pathology, 2018)

Regulation of myostatin expression is associated with growth and muscle development in commercial broiler and DMC muscle - Tengfei Dou; Zhengtian Li; Kun Wang; Lixian Liu; Hua Rong; Zhiqiang Xu; Ying Huang; Dahai Gu; Xiaobo Chen; Wenyuan Hu; Jiarong Zhang; Sumei Zhao; et al. (Molecular Biology Reports, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Changes by cadmium stress in lipid peroxidation and activities of lipoxygenase and antioxidant enzymes in Arabidopsis are associated with extracellular ATP - Qin-zheng Hou; Guang-ji Ye; Rong-fang Wang; Ling-yun Jia; Jun-yu Liang; Han-qing Feng; Jing Wen; Dai-long Shi; Qing-wen Wang (Biologia, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Globular adiponectin inhibits leptin-stimulated esophageal adenocarcinoma cell proliferation via adiponectin receptor 2-mediated suppression of UHRF1 - Jun Wang; Yan Cheng; Xiaoran Yin; Jie Wu; Yumei Luo; Jing Wu; Jia Di; Dong Liu; Yahui Huang; Rong Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Personal exposure to PM2.5 associated with heavy metals in four travel modes of Tianjin during the summer season - Bao Qing Wang; Jian Feng Liu; Bo Wei Liu; Hong Hong Niu; Rong Hui Chen; Ze Bei Wang; Jia Jia Zhao; Zi Hui Ren (Environmental Science and Pollution Research, 2017)

Changes in mean and extreme temperature and precipitation over the arid region of northwestern China: Observation and projection - Yujie Wang; Botao Zhou; Dahe Qin; Jia Wu; Rong Gao; Lianchun Song (Advances in Atmospheric Sciences, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Repeated pre-training sleep restriction in adolescent rats impaired spatial performance - Su-Rong Yang; Huan-Xin Sun; Zhen-Zhen Hu; Si-Heng Wang; Hui Sun; Yin-Jia Xue; Chen-Bo Ye (Sleep and Biological Rhythms, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Effects of β-glucan on ROS production and energy metabolism in yellow croaker (Pseudosciaena crocea) under acute hypoxic stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Jia-Lang Zheng; Chang-Wen Wu; Rong Cai (Fish Physiology and Biochemistry, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Pseudomonas syringae pv. Actinidiae isolated from non-kiwifruit plant species in China - Pu Liu; Shizhou Xue; Rong He; Jiayong Hu; Xiaojie Wang; Bing Jia; Lorenzo Gallipoli; Angelo Mazzaglia; Giorgio M. Balestra; Liwu Zhu (European Journal of Plant Pathology, 2016)

Microbial community characteristics during simultaneous nitrification-denitrification process: effect of COD/TP ratio - Jian Zhang; Wenlin Jia; Rong Wang; Huu Hao Ngo; Wenshan Guo; Huijun Xie; Shuang Liang (Environmental Science and Pollution Research, 2016)

Heavy metals in wild marine fish from South China Sea: levels, tissue- and species-specific accumulation and potential risk to humans - Jin-Ling Liu; Xiang-Rong Xu; Zhen-Hua Ding; Jia-Xi Peng; Ming-Hua Jin; You-Shao Wang; Yi-Guo Hong; Wei-Zhong Yue (Ecotoxicology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Purification and Antioxidant Property of Antioxidative Oligopeptide from Short-Necked Clam ( Ruditapes philippinarum ) Hydrolysate In Vitro - Rong Li; Zui-su Yang; Yu Sun; Li Li; Jia-Bin Wang; Guofang Ding (Journal of Aquatic Food Product Technology, 2015)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Organochlorine pesticides and their metabolites in human breast milk from Shanghai, China - Dasheng Lu; Dongli Wang; Rong Ni; Yuanjie Lin; Chao Feng; Qian Xu; Xiaodong Jia; Guoquan Wang; Zhijun Zhou (Environmental Science and Pollution Research, 2015)

Effects on Pharmacokinetics of Propranolol and Other Factors in Rats After Acute Exposure to High Altitude at 4,010 m - Li Wenbin; Wang Rong; Xie Hua; Zhang Juanhong; Wu Xiaoyu; Jia Zhengping (Cell Biochemistry and Biophysics, 2015)

The Effect of Continuous Blood Purification on the Prognosis of Cardiorenal Syndrome Patients - Fengyu Jia; Peng Rong; Dandan Li; Suxia Wang; Ying Jing; Yanming Ge; Jianzhong Meng (Cell Biochemistry and Biophysics, 2015)

Rainfall and tillage impacts on soil erosion of sloping cropland with subtropical monsoon climate — A case study in hilly purple soil area, China - Jia-liang Tang; Xun-qiang Cheng; Bo Zhu; Mei-rong Gao; Tao Wang; Xi-feng Zhang; Pei Zhao; Xiang You (Journal of Mountain Science, 2015)

Heavy metal and organic contaminants in mangrove ecosystems of China: a review - Zai-Wang Zhang; Xiang-Rong Xu; Yu-Xin Sun; Shen Yu; Yong-Shan Chen; Jia-Xi Peng (Environmental Science and Pollution Research, 2014)

Changes in weathering effectiveness and community of culturable mineral-weathering bacteria along a soil profile - Qi Wang; Rong Rong Wang; Lin Yan He; Jia Jia Lu; Zhi Huang; Xia Fang Sheng (Biology and Fertility of Soils, 2014)

Studies on the analgesic activities of Jia-Yuan-Qing pill and its safety evaluation in mice - Ye Tian; Li-rong Teng; Jing-jing Song; Qing-fan Meng; Jia-hui Lu; Wei-wei Zhang; Kang Wei; Ning Wang; Di Wang; Le-sheng Teng (Protoplasma, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Cloning and characterization of squalene synthase gene from Poria cocos and its up-regulation by methyl jasmonate - Jian-Rong Wang; Jun-Fang Lin; Li-Qiong Guo; Lin-Feng You; Xian-Lu Zeng; Jia-Ming Wen (World Journal of Microbiology and Biotechnology, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Effect of Hyperoxia on the Viability and Proliferation of the Primary Type II Alveolar Epithelial Cells - Xiu-xiang Liu; Xiu-rong Yu; Xiu-hong Jia; Ke-xuan Wang; Zheng-yan Yu; Chang-jun Lv (Cell Biochemistry and Biophysics, 2013)

Determination of Concentration of Methotrexate Enantiomers in Intracellular and Extracellular Fluids of HepG2 Cells by Liquid Chromatography–Tandem Mass Spectrometry - Rong Wang; Lifang Guo; Hua Xie; Juanhong Zhang; Xiaoyun Li; Wenbing Li; Jianfeng Wang; Xiaoyu Wu; Zhengping Jia (Cell Biochemistry and Biophysics, 2013)

Immobilization of trace metals by phosphates in contaminated soil near lead/zinc mine tailings evaluated by sequential extraction and TCLP - Wei-Hong Wu; Zheng-Miao Xie; Jian-Ming Xu; Fan Wang; Jia-Chun Shi; Rong-Bin Zhou; Zan-Fang Jin (Journal of Soils and Sediments, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Survey of aflatoxin M1 in raw milk in the five provinces of China - Nan Zheng; Jia-Qi Wang; Rong-Wei Han; Yun-Peng Zhen; Xiao-Min Xu; Peng Sun (Food Additives & Contaminants Part B-Surveillance, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

Pharmacokinetics Study of Amoxycillin and Clavulanic acid (8:1)-A New Combination in Healthy Chinese Adult Male Volunteers Using the LC–MS/MS Method - Juanhong Zhang; Yinfu Wang; Hua Xie; Rong Wang; Zhengping Jia; Xiandong Men; Liting Xu; Qiang Zhang (Cell Biochemistry and Biophysics, 2013)

The contribution of intersubspecific hybridization to the breeding of super-high-yielding japonica rice in northeast China - Jian Sun; Di Liu; Jia-Yu Wang; Dian-Rong Ma; Liang Tang; Hong Gao; Zheng-Jin Xu; Wen-Fu Chen (Theoretical and Applied Genetics, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Polymorphism of CAG repeats in androgen receptor of carnivores - Qin Wang; Xiuyue Zhang; Xiaofang Wang; Bo Zeng; Xiaodong Jia; Rong Hou; Bisong Yue (Molecular Biology Reports, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Relationship between transmembrane signal transduction pathway and DNA repair and the mechanism after global cerebral ischemia-reperfusion in rats - Rong-Liang Xue; Jia-Xuan He; Ning Wang; Feng-Zhen Yao; Jian-Rui Lv; Gang Wu (Neuroscience Bulletin, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Molecular cloning and characterization of twoBrassica napus TTG1 genes reveal genus-specific nucleotide preference, extreme protein-level conservation and fast divergence of organ-specificity - Jun Lu; Jia-Na Li; Bo Lei; San-Gen Wang; You-Rong Chai (Genes & Genomics, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Distribution, biomass, and dynamics of roots in a revegetated stand of Caragana korshinskii in the Tengger Desert, northwestern China - Zhi-Shan Zhang; Xin-Rong Li; Li-Chao Liu; Rong-Liang Jia; Jing-Guang Zhang; Tao Wang (Journal of Plant Research, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Phytase expression in transgenic soybeans: stable transformation with a vector-less construct - Xiao Rong Gao; Guo Kun Wang; Qiao Su; Yan Wang; Li Jia An (Biotechnology Letters, 2007)

Berbamine induces apoptosis in human hepatoma cell line SMMC7721 by loss in mitochondrial transmembrane potential and caspase activation - Guan-yu Wang; Jia-wei Zhang; Qing-hua Lü; Rong-zhen Xu; Qing-hua Dong (Journal of Zhejiang University-SCIENCE B, 2007)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

Bone marrow mesenchymal stem cell transplantation combined with perindopril treatment attenuates infarction remodelling in a rat model of acute myocardial infarction - Jian-an Wang; Rong-hua Luo; Xing Zhang; Xiao-jie Xie; Xin-yang Hu; Ai-na He; Jie Chen; Jia-hui Li (Journal of Zhejiang University-SCIENCE B, 2006)

Molecular cloning and characterization of betaine aldehyde dehydrogenase gene from Suaeda liaotungensis and its use in improved tolerance to salinity in transgenic tobacco - Qiu-Li Li; Xiao-Rong Gao; Xiao-Hong Yu; Xing-Zhi Wang; Li-Jia An (Biotechnology Letters, 2003)